The pathophysiology and therapeutic approaches in retinitis pigmentosa - Sariningsih, Suryanita (International Journal of Research in Medical Sciences, 2024)
Retinitis Pigmentosa is a prevalent hereditary retinopathy that involves the gradual deterioration of vision cells and the disturbance of retinal pigment epithelium. The typical triad of retinitis pigmentosa is the pigmentation of the bone spicules, blood vessel constriction, and pallor of the optic nerve. The variety of clinical presentations is nyctalopia, tunnel vision, loss of colour discrimination, and in a later stage, complete loss of visual acuity. The immense genetic mutation accounts for the pathogenesis of RP. This diverse mutation makes treatment exceptionally challenging for RP. Until now, there is no specific therapy recommended for RP. Gene therapy is possibly the best option for RP, but further clinical trials are needed to provide customized therapy for each patient. Various therapeutic trials use pharmacologic agents such as neurotrophic, anti-apoptotic, antioxidant, anti-inflammatory, and anti-VEGF also use to postpone the progressivities of RP.